A change in phytoplankton community index with water quality improvement in Tolo Harbour, Hong Kong. (February 2018) - Lei, Yue; Whyte, Callum; Davidson, Keith; Tett, Paul; Yin, Kedong
Abstract: Water quality in Tolo Harbour and Channel (Tolo) has been improved since 1998 after the diversion of sewage effluent. However, it remains poorly understood how nutrient loading reduction has impacted the phytoplankton community. To evaluate this, we applied a Phytoplankton Community Index PI(mp) to the 23-year data (1991–2013) at inner (TM4) and outer (TM8) sites in Tolo, with the former being more eutrophic than the latter. The results show that 1) the phytoplankton community changed with time after sewage diversion; 2) "diatoms and dinoflagellates" were better indicators of nutrient impact than "autotrophic/mixotrophic and heterotrophic dinoflagellates"; 3) the rate of recovery differed between the two stations, but both reached a similar state at a similar time; 4) seasonality of the phytoplankton community showed greater disturbance in spring than in other seasons. Our findings indicate that the nutrient reduction in the Tolo resulted in a positive change in the phytoplankton community. Highlights: The phytoplankton community changes with time after sewage diversion. "Diatoms vs dinoflagellates" is a better indicator than "autotrophic/mixotrophic vs heterotrophic dinoflagellates". Recovery of community structure differs between stations but both eventually reaches a similar state. Disturbance to community is greater in spring than in other seasons.